Impact of technology integration on students’ sense of belonging and well-being: a systematic review - Folabit, Novel Lena; C. Jita, Loyiso; Jita, Thuthukile (Institute of Advanced Engineering and Science, 2025)
As an important tool, technology supports and enhances students’ educational experiences by fostering inclusive learning communities, bridging cultural gaps, and accommodating diverse learning styles. However, limited studies have demonstrated the impact of technology integration on students’ sense of belonging and well-being in the context of South African higher education. This study aimed to address this gap through a systematic literature review. Published scholarly peer-reviewed articles were used to examine the impact of technology on students’ sense of belonging and well-being. The technology acceptance model (TAM) and self-determination theory (SDT) were used to theorize the findings. The findings reveal that while technology provides self-directed learning, it also exacerbates inequalities and digital stress. In addition, factors affecting students’ sense of belonging and well-being include the digital divide, isolation-related stress, and psychological needs due to a lack of technology preparedness, compounded by socio-economic disparities and insufficient digital skills and technical support. It is recommended that global financial, technical, and intellectual stakeholders collaborate to ensure equal access to digital resources in education. These strategies should focus on supporting user-friendly initiatives that bridge the digital gap. The study limitations include reliance on existing literature and lack of direct student feedback.